The Inhibition of Ocean Acidification on the Formation of Oyster Calcified Shell by Regulating the Expression of Cgchs1 and Cgchit4 - Zhang, Yukun; Liu, Zhaoqun; Song, Xiaorui; Huang, Shu; Wang, Lingling; Song, Linsheng (Frontiers in Physiology, 2019)
The biosynthesis of a calcified shell is critical for the development of oyster larvae. This process can be severely inhibited by CO2-induced ocean acidification, causing mass mortality of oyster larvae. However, the underlying molecular mechanism of such process has not been well explored until now. In the present study, a homologue of chitin synthase (named as Cgchs1) and a homologue of chitinase (named as Cgchit4) were identified from the Pacific oyster Crassostrea gigas. The cDNA sequences of Cgchs1 and Cgchit4 were of 813 bp and 2118 bp, encoding a putative polypeptide of 271 amino acids and 706 amino acids, respectively. There were a Chitin_synth_2 domain and a Glyco_18 domain in the inferred amino acid sequences of Cgchs1 and Cgchit4, respectively. Both Cgchs1 and Cgchit4 shared high sequence identity with their homologues in vertebrates. In addition, when oyster larvae were exposed to acidification treatment (pH 7.4), their shell biosynthesis process was seriously restrained. The expression level of Cgchs1 mRNA was significantly suppressed while that of Cgchit4 was dramatically activated upon acidification treatment. Cgchs1 and Cgchit4 are critical enzymes for chitin metabolism, and such changes in their mRNA expression could result in the decrease of chitin content in oyster larvae’s shells, which might lead to the failure of shell formation. Therefore, results in the present study suggested that acidified seawater might inhibit the formation of oyster calcified shell by suppressing the biosynthesis of chitin.